Cytotoxic and anti-human papillomavirus activites in selected vegetables / Maizatul Azmah binti Ab. Latiff - Ab. Latiff, Maizatul Azmah (2010)

(untitled)
An appropriate way to control cancer is chemoprevention as a large number of compounds have been observed to prevent the occurrence of cancer and variety of mechanisms exists for producing such protective effects. Numerous epidemiological studies have shown that diets rich in vegetables are associated with a decreased risk of cancer. Chemoprevention involves the use of natural or laboratory made substances to prevent cancer or reduce risk cancer.The E6 oncoprotein from oncogenic Human papillomaviruses (HPVs) has exhibit functions in tumorigenesis, regulation of transcriptions and apoptosis. E6 product from oncogenic viral type like HPV 16 can bind the tumor suppressor p53 and promotes its degradation. In the present study, 80 crude methanol and water extracts obtained from 40 selected vegetables were screened and evaluated for their cytotoxic and anti-human papillomavirus 16 E6 activities.The cytotoxic effect of the varying concentrations of both methanol and water vegetable extracts (0, 1, 10, 25, 50 and 100 μg/ml) against cervical cancer-derived, HeLa and CaSki cells and normal cell-derived, MRC5 (human lung fibroblast) cells were evaluated using the in vitro neutral red cytotoxic assay. The IC50 values for each vegetable extract was determined. The results indicated that the percentage of killing increased with the increasing concentration of extracts tested. Overall, the crude methanol vegetable extracts showed greater inhibition against the growth of cervical cancer-derived cell lines, HeLa and CaSki cells. The methanolic vegetable extracts exerted signs of cell-type selectivity against cervical cancer-derived cell lines where 29 extracts were active against CaSki. However, only 7 extracts were effective in inhibiting the growth of HeLa cells.Twenty vegetable extracts, both methanol and water extracts of Asparagus officinalis, Beta vulgaris, Ipomea batatas, Manihot esculentus, Pachyrrizus erosus,Petroselium crispum, Phaseolus vulgaris, Portulaca oleracea, Sesbania grandiflora, and Solanum tuberosum were analyzed qualitatively at various concentrations (0, 1, 10, 25, 50 and 100 μg/ml) for their anti-HPV 16 E6 in HPV 16 containing, cervical cancer-derived cell line, CaSki. Immunocytochemistry technique was carried out to analyze the expression of HPV 16 E6 oncoprotein in CaSki cells treated with varying amounts of the vegetable extracts. The results indicated that methanolic extracts of Phaseolus vulgaris suppression of E6 oncoprotein in CaSki cells which increased in cells treated independently with increasing concentrations of the vegetable extracts. Generally, the crude water extracts were most effective in suppressing the expression of HPV 16 E6 oncoprotein in CaSki cells. The results of the present study indicated that out of the 40 selected vegetables screened, Portulaca oleracea (Beremi) and Beta vulgaris (Beetroot) showed significant cytotoxic effects and anti-HPV 16 E6 activities in CaSki cells. These findings suggest that some of the vegetables may tested have great potential to be exploited for effective chemoprevention and as anti-HPV 16 E6 agent in the control of cervical cancer.